Laboratory Algorithm in HIV Infection Diagnosis - Uğur Tüzüner; Begüm Saran Gülcen; Mehmet Özdemir (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2016)
AIDS caused by HIV is an infection disease which was defined firstly in the USA in 1981. Since then, number of AIDS patients has increased continuously. About 36.9 million people are living with HIV around the world. Approximately 15 million people living with HIV were receiving antiretroviral therapy. Early detection is important due to the high risk of transmission that precedes seroconversion and also because it provides an opportunity to improve health outcomes with an early antiretroviral therapy. HIV testing is the key part of diagnosis and prevention efforts. Many tests have been used in the diagnosis of HIV over years and with developing testing methods, accuracy of the laboratory diagnosis of HIV infection has been improved. Detecting p24 antigens, HIV 1-2 antibodies and HIV nucleic acid demonstrated that antibody testing alone might miss a considerable percentage of HIV infections detectable by these tests. This review provides updated recommendations and algorithm for HIV testing that are necessary for diagnosing HIV and offers approaches for accurate assessment of test results.